Pengembangan Silabus Bahasa - Muhammad Farkhan (Buletin Al-Turas, 2005)
Language syllabus can be defined as a general outline of the language teaching program which guides a teacher what to teach and how to teach in a language program. It,of course, should consist of the approach to apply, materials to teach, the techniques to implement, learning resources to use, and the methods of evaluation to apply. Therefore, it should be developed as completely as possible to provide the teacher with good teaching guidance. Developing a language syllabus involves three main stages: preparation, data collection and analysis, and finishing. Preparation refers to the understanding of philosophical and social factors. Data collection and analysis refers to the activities of designing an instrument and analyzing the collected data using the principles and theories adopted. Finishing refers to the establishment of the syllabus as stipulated by the intended language program.